Multidimensional Perspectives on Temporary Architecture: Exploring the Social, Political, and Economic Impacts through the Case Study of Leishenshan Hospital - Li, Bin (International Journal of Global Economics and Management, 2024)
This paper explores the use of temporary buildings in COVID-19 emergencies, focusing on Leishenshan Hospital in Wuhan. Data sources include literature, technical staff, and expert interviews. It highlights modular construction, BIM technology, adaptability, sustainability, and teamwork. The conclusion emphasizes modular construction and BIM technology’s role in accelerating projects, while noting the importance of considering socio-cultural and environmental impacts.